2017
DOI: 10.5152/eurasianjmed.2017.16262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microorganisms Causing Ventilator-Associated Pneumonia in a Pediatric Intensive Care Unit

Abstract: Objective: The aim of this study was to identify microorganisms causing ventilator-associated pneumonia (VAP) and also study the antibiotic resistance/susceptibility. Materials and Methods:We retrospectively assessed microorganisms isolated from patients diagnosed with VAP in a pediatric intensive care unit between January 1, 2014, and June 30, 2016. Results:We included 44 patients diagnosed with VAP. The prevalence thereof was 8.6 patients per 1,000 ventilator days. Mechanical ventilation was required for 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
5
9
0
1
Order By: Relevance
“…The current study results showed that more than half of VAP infants received inadequate general infection control measures and the vast majority of non VAP infants received adequate infection control, these results were in accordance with [27,45] who reported that, poor adherence to hand hygiene infection control processes can lead to cross contamination of organisms between children and this may contribute to VAP development. Also, the current study results were in accordance with a study done by [46] in Egypt about "reducing ventilator-associated pneumonia in neonatal Intensive Care Unit using VAP prevention bundle: A cohort study" who recommended that, hand hygiene is the most important infection control intervention in all health care setting and stated that applying bundle of infection control practices can effectively reduce the occurrence of VAP during neonatal ventilation period.…”
Section: Discussionsupporting
confidence: 91%
“…The current study results showed that more than half of VAP infants received inadequate general infection control measures and the vast majority of non VAP infants received adequate infection control, these results were in accordance with [27,45] who reported that, poor adherence to hand hygiene infection control processes can lead to cross contamination of organisms between children and this may contribute to VAP development. Also, the current study results were in accordance with a study done by [46] in Egypt about "reducing ventilator-associated pneumonia in neonatal Intensive Care Unit using VAP prevention bundle: A cohort study" who recommended that, hand hygiene is the most important infection control intervention in all health care setting and stated that applying bundle of infection control practices can effectively reduce the occurrence of VAP during neonatal ventilation period.…”
Section: Discussionsupporting
confidence: 91%
“…In 2017 and 2018, 2 cases of XDR A. faecalis pneumonia were reported by Agarwal and Junejo [22,23]. In 2019, Hasan reported a 60-year-old female with pandrugresistant A. faecalis bacteremia who was treated with double-dose tigecycline, and had a successful treatment outcome [26]. It was terrible that a pandrug-resistant A. faecalis pathogen had been found.…”
Section: The Trend Of Antibiotic Sensitive Rate Of a Faecalismentioning
confidence: 99%
“…By endotracheal culture, the causative organism is found and an antibiotic is chosen according to the result of culture. The most common organisms are Pseudomonas aeruginosa, Klebsiella pneumonia, Acinetobacter baumannii [50], Serratia marcescens [51] and methicillin-resistant Staphylococcus aureus [52]. Chest radiograph accompanied by clinical and laboratory findings are required for diagnosis of patients with suspected VAP [53].…”
Section: Diagnosismentioning
confidence: 99%